PENGATURAN SANKSI PIDANA PENYALAHGUNAAN NARKOBA BAGI ANAK DI BAWAH UMUR - Hartanti; Jalu Pangestu; Endah Noor Jati; Anas Miftahul Huda; Viviana Lorossae; Petrus Tahta Anggriawan Putra Semana (Kajian Hukum, 2022)
Children are part  a nation  for the next generation. Children have the right to get protection from various types of threats that endanger them, including the practice of drug abuse. Drugs are substances or drugs,  from plants and other, which are made periodically in the process of synthesis and non-synthesis, which in their use can cause effects such as decreased consciousness, loss of taste, and can cause users  experience dependence. The purpose of this study is to determine the regulations governing the criminal sanctions for drug abuse for minors. This research uses  qualitative method with a statutory approach. The data used is secondary data in the form of data on cases of children in 2019-2021 obtained through documents of the National Narcotics Agency of the Special Region Yogyakarta. Drug abuse involving minors involved the role of children as drug couriers or drug users, aged between 16-17 years. The first suspect was arrested for a criminal act as a methamphetamine courier, while the second and third suspects were arrested for using gorilla tobacco purchased through online trading. The legal basis for sanctions for narcotics abuse is regulated in Law No. 35 of 2009 and Law No. 11 of 2012.